Sentence comprehension and morphological cues in aphasia: What eye-tracking reveals about integration and prediction. (May 2015) - Hanne, Sandra; Burchert, Frank; De Bleser, Ria; Vasishth, Shravan
Abstract: Comprehension of non-canonical sentences can be difficult for individuals with aphasia (IWA). It is still unclear to which extent morphological cues like case marking or verb inflection may influence IWA's performance or even help to override deficits in sentence comprehension. Until now, studies have mainly used offline methods to draw inferences about syntactic deficits and, so far, only a few studies have looked at online syntactic processing in aphasia. We investigated sentence processing in German-speaking IWA by combining an offline (sentence-picture matching) and an online (eye-tracking in the visual-world paradigm) method. Our goal was to determine whether IWA are capable of using inflectional morphology (number-agreement markers on verbs and case markers in noun phrases) as a cue to sentence interpretation. We report results of two visual-world experiments using German reversible SVO and OVS sentences. In each study, there were eight IWA and 20 age-matched controls. Experiment 1 targeted the role of unambiguous case morphology, while Experiment 2 looked at processing of number-agreement cues at the verb in case-ambiguous sentences. IWA showed deficits in using both types of morphological markers as a cue to non-canonical sentence interpretation and the results indicate that in aphasia, processing of case-marking cues is more vulnerable as compared to verb-agreement morphology. We ascribe this finding to the higher cue reliability of agreement cues, which renders them more resistant against impairments in aphasia. However, the online data revealed that IWA are in principle capable of successfully computing morphological cues, but the integration of morphological information is delayed as compared to age-matched controls. Furthermore, we found striking differences between controls and IWA regarding subject-before-object parsing predictions. While in case-unambiguous sentences IWA showed evidence for early subject-before-object parsing commitments, they exhibited no straightforward subject-first prediction in case-ambiguous sentences, although controls did so for ambiguous structures. IWA delayed their parsing decisions in case-ambiguous sentences until unambiguous morphological information, such as a subject-verb-number-agreement cue, was available. We attribute the results for IWA to deficits in predictive processes based on morpho-syntactic cues during sentence comprehension. The results indicate that IWA adopt a wait-and-see strategy and initiate prediction of upcoming syntactic structure only when unambiguous case or agreement cues are available.